THE ROLE OF CEREBROSPINAL FLUID PRESSURE IN GLAUCOMA - Исаков, Иван Николаевич (Medicine in Kuzbass, 2019)
The article is a review of domestic and foreign literature on the problem of the influence of the level of pressure of cerebrospinal fluid on the level of translaminar pressure gradient. It is assumed that such changes in pressure can have a negative effect on the state of the optic nerve head and lead to the development of glaucomatous optic neuropathy. This phenomenon, according to a number of authors, is an explanation of the development of changes in the optic nerve characteristic of glaucoma in individuals with normal IOP. Similarly, individuals with ophthalmic hypertension and elevated cerebrospinal fluid pressure will have a kind of protection against alteration of the optic nerve head. The literature data suggest that the retrolaminar tissue pressure in the optic disc is mainly determined by the level of pressure of the cerebrospinal fluid.Conclusions. Intracranial pressure along with intraocular pressure forms a transmembrane gradient of tissue pressure in the optic nerve.
Keywords: cerebrospinal fluid; glaucomatous optic neuropathy; retrolaminar tissue pressure; ophthalmic hypertension; glaucoma